Development of a Digital English Module for Students to Improve Text Reading Skills at the Sekolah Tinggi Ilmu Ekonomi Pembangunan Nasional Malang - Yuliyanto Sabat; Abd. Syakur; Tri Achmad Budi Susilo; I Made Darsana (⁠International Journal of Asia Pacific Community Service, 2024)
The integration of digital technology in university-level English language learning is vital for enhancing student engagement and interaction. This research develops Digital Modules using the R&D method and the R2D2 model, including stages of definition, development, and dissemination. Designed to be self-contained, independent, adaptive, and user-friendly, the modules meet modern educational needs. Evaluations by media experts, subject matter experts, and students scored 88.5%, 93.1%, and 92.6%, respectively, indicating that the modules are effective without requiring revisions. The modules aim to improve text reading skills through various activities, multimedia elements, and different text formats like news articles and essays. Conducted with 65 undergraduate Management students at the International Institute of Tourism and Business, the study shows significant improvements in reading skills. The modules are highly accessible, facilitating independent learning and enhancing material comprehension. The developed digital modules are suitable and effective for English language learning, meeting all objectives and criteria.